The Treatment Based on Ruxolitinib and Amphotericin B is Effective for Relapsed Leishmaniasis-Related Hemophagocytic Lymphohistiocytosis: A Case Report and Literature Review - Cui T; Wang J; Wang Z (Infection and Drug Resistance, 2022)
Tingting Cui, Jingshi Wang, Zhao Wang Department of Hematology, Beijing Friendship Hospital, Capital Medical University, Beijing, 100050, People’s Republic of ChinaCorrespondence: Zhao Wang, Department of Hematology, Beijing Friendship Hospital, Capital Medical University, Beijing, 100050, People’s Republic of China, Tel +86-10-63138303, Email wangzhao@ccmu.edu.cnBackground: Hemophagocytic lymphohistiocytosis (HLH) is known as a life-threatening syndrome, and Leishmania is the most common protozoan that triggers infection-related HLH. It is thus important to find the root cause and treat it effectively.Case Report: This paper reports a 44-year-old man who developed antisynthetase antibody syndrome previously. The patient progressed rapidly to the extent of meeting the HLH-2004 diagnostic criteria, despite the unknown etiology. Although the patient was promptly treated in line with the HLH-1994 protocol to achieve remission, he still relapsed after glucocorticoid reduction. Afterwards, it was found out that HLH was secondary to Leishmania infection. The symptoms of HLH were alleviated quickly by the treatment with Ruxolitinib and Amphotericin B.Conclusion: Etiological screening plays a crucial role in leishmaniasis-related HLH. An experienced pathologist and real-time PCR are essential for treating Leishmania. The treatment of Ruxolitinib and Amphotericin B proved effective in alleviating the relapse of visceral leishmaniasis-related HLH.Keywords: hemophagocytic lymphohistiocytosis, visceral leishmaniasis, Amphotericin B, Ruxolitinib